A REVISION OF THE PALEOZOIC BRYOZOAN GENERA SYNOCLADIA AND THAMNISCUS - Lisitsyn D.V.; Ernst A. (My University, 2004)
New data on the morphology of the genera Synocladia and Thamniscus are presented, and the diagnoses and species composition of these genera are revised. A new genus, Synocladiella Lisitsyn, and a new species, Thamniscus perplexus Ernst, designated as the type species of the genus Thamniscus in place of Th. dubius, which was erroneously determined by King when establishing the genus Thamniscus, are described.
Keywords: Synocladia; Paleozoic; Paleozoic; Палеозой